Emergence of Resistance to Colistin During the Treatment of Bloodstream Infection Caused by Klebsiella pneumoniae Carbapenemase–Producing Klebsiella pneumoniae. (23rd April 2018) - Kanwar, Anubhav; Marshall, Steven H; Perez, Federico; Tomas, Myreen; Jacobs, Michael R; Hujer, Andrea M; Domitrovic, T Nicholas; Rudin, Susan D; Rojas, Laura J; Kreiswirth, Barry N; Chen, Liang; Quinones-Mateu, Miguel; et al.
Abstract: We report the emergence of colistin resistance in Klebsiella pneumoniae carbapenemase (KPC)–producing Klebsiella pneumoniae after 8 days of colistin-based therapy, resulting in relapse of bloodstream infection and death. Disruption of the mgrB gene by insertion of a mobile genetic element was found to be the mechanism, which was replicated in vitro after exposure to subinhibitory concentrations of colistin and meropenem.